Chronic Lymphedema of the Lower Limb: A Rare Cause of Dislocation of Total Hip Arthroplasty - Vaishya, Raju (Cureus, 2016)
Total hip arthroplasty (THA) in a patient with chronic lymphedema of both lower limbs is rarely reported in the literature. Chronic lymphedema is a challenging condition associated with various complications especially in a patient with THA. However, dislocation of the total hip prosthesis due to acute exacerbation of lower limb swelling in the postoperative period is an extremely rare complication. The cause that led to the dislocation of the prosthesis is intricate and difficult to assess, as this has not been discussed in the literature yet. We believe that the excessive weight of the limb due to chronic lymphedema had a deleterious effect on the biomechanics of total hip prosthesis, thereby increasing the tendency for dislocation. This case illustrates that chronic lymphedema of the lower limb should be dealt with aggressively using various modalities like intermittent pneumatic compression pumps and compression stockings after THA in such patients.